2004
DOI: 10.2175/193864704784147700
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Process Modeling to Investigate the Performance of a Large Industrial Wastewater Treatment Plant

Abstract: The ASM3 model as implemented in the GPS-X wastewater treatment plant simulator was used to model a wastewater treatment plant operated by the Eastman Chemical Company that treats waste from a chemical production plant. The Kingsport plant is a step-feed activated sludge plant with conventional secondary clarification. The composition of the influent waste stream was highly variable during the study period and this required special attention when characterizing the influent in terms of the ASM3 state variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…These plots are for the entire 2002 operating period considered (January 1, 2002 to November 12, 2002). For a more detailed discussion of the calibration results see Schraa et al (2004). Based on the calibration results the project team concluded that the model could adequately predict plant performance and was suitable for analyzing plant operation and performing "what-if" simulations.…”
Section: Model Setup and Calibrationmentioning
confidence: 99%
“…These plots are for the entire 2002 operating period considered (January 1, 2002 to November 12, 2002). For a more detailed discussion of the calibration results see Schraa et al (2004). Based on the calibration results the project team concluded that the model could adequately predict plant performance and was suitable for analyzing plant operation and performing "what-if" simulations.…”
Section: Model Setup and Calibrationmentioning
confidence: 99%
“…Existing activated sludge process (ASP) models can be used to model industrial WWTPs (e.g. Bury et al, 2002;Goodfellow et al, 2004;Schraa et al, 2004;Stricker and Racault, 2005;Takács et al, 1998), but model customization may be required to handle pollutants not commonly found in domestic wastewater. Direct application of the existing models is often possible in industries such as food processing (Snowling and Malyk, 2002), but…”
Section: Introductionmentioning
confidence: 99%